La eficacia de la legislación ecuatoriana en el cumplimiento del derecho de protección familiar del adulto mayor bajo el enfoque de la solidaridad intergeneracional - Ichau Cajas, Evelyn Tatiana (2022)
This paper is entitled: 'The effectiveness of Ecuadorian legislation in fulfilling the right of family protection of the elderly under the focus of intergenerational solidarity' (2014- 2021) It analyses how the right to family protection of the elderly is guaranteed in both its internal and external individual spheres. Understanding the individual and collective connotation of the right to family protection of the elderly also means safeguarding the age group in the same way that children and adolescents are protected through alimony (which in the case of the elderly may acquire another name). Once the right to family protection of the elderly is guaranteed, constitutional rights are also guaranteed from the family and then from the State level. The general objective of this research is: To analyze the effectiveness of Ecuadorian legislation in fulfilling the right of family protection of the elderly under the focus of intergenerational solidarity. To that end, the methods used have been the normative and synthetic analytical method, which will serve to identify the international and national norms applicable to the right to family protection of the elderly in Ecuador from 2010 to 2021\; to determine whether or not this right has existed in Ecuador\; and, to examine compliance with this right through the documentary analysis of Case No. 17203-2018-02940, through the instrument of the bibliographical data sheet. The main conclusion that has been drawn is that Ecuadorian legislation has not been effective in protecting the right to family protection of the elderly between 2010 and 2021.